Laminated films and image display devices
Patent Information
- Application Number
- CN202580021035.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-15
- Filing Date
- 2025-03-14
- Publication Date
- 2026-10-27
AI Technical Summary
[0046]根据本公开,能发挥能提供一种耐擦伤性优异的层叠膜的效果。
Smart Images

Figure CN122995944A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to laminated films and image display devices. Background Technology
[0002] Films with textured surfaces are widely used in waterproof membranes, anti-glare membranes, and writing feel-enhancing membranes for touch panels.
[0003] For example, Patent Document 1 describes a writing feel enhancement film that achieves a writing feel similar to that of writing on paper with a pencil or pen by having large and small protrusions present on the surface at a specific density.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-097670 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] However, the scratch resistance of existing products cannot be said to be sufficient. For the writing feel enhancement film described in Patent Document 1, when repeated input using a stylus, scratches may sometimes appear on the surface, or the surface may become uneven and worn due to wear, gradually making it impossible to obtain the desired writing feel.
[0009] The technical problem of this disclosure is to provide a laminated film with excellent scratch resistance.
[0010] Solution for solving the problem
[0011] To solve the aforementioned technical problems, the inventors conducted repeated and in-depth research. Their findings revealed that by adjusting the area occupancy of the protrusions on the surface of the laminated film, the scratch resistance of the laminated film can be improved. That is, the main points of this disclosure are as follows.
[0012] 〔1〕
[0013] A laminated film comprising: a substrate layer; and a resin layer formed on the substrate layer, wherein the opposite side of the substrate layer is a surface with an uneven shape, wherein when the surface shape of the uneven surface is measured by an optical interference surface shape measuring device at a measurement area of 189.46 μm × 252.5 μm, the average area occupancy of the protrusions with a height of 0.3 μm or more is 6% or more, and when the uneven surface is subjected to an abrasion resistance test using an abrasion wheel under the conditions of a load of 750 g, a sliding distance of 5 cm, a sliding speed of 40 reciprocations / minute, and 100 reciprocations, the laminated film satisfies one or more of the following (a) to (d).
[0014] (a) B1 / A1≥0.80
[0015] (b) B2 / A2 ≥ 0.60
[0016] (c) B3 / A3 ≥ 0.60
[0017] (d) B4 / A4 ≥ 0.60
[0018] (In equations (a) to (d), A1 is the two-dimensional average roughness Ra of the roughness curve elements of the uneven surface before the wear resistance test. B1 is the two-dimensional average roughness Ra of the roughness curve elements of the uneven surface after the wear resistance test; A2 is the maximum height Rz of the roughness curve element of the uneven surface before the wear resistance test; B2 is the maximum height Rz of the roughness curve element of the uneven surface after the wear resistance test; A3 represents the average unevenness height Rc of the roughness curve elements of the uneven surface before the wear resistance test; B3 is the average unevenness height Rc of the roughness curve element of the uneven surface after the wear resistance test; A4 represents the ten-point average roughness Rzjis of the roughness curve elements of the uneven surface before the wear resistance test. B4 represents the ten-point average roughness Rzjis of the roughness curve elements of the uneven surface after the wear resistance test.
[0019] 〔2〕
[0020] According to the laminated film described in [1], the number of scratches with a width of 0.1 mm or more and a length of 1.0 mm or more produced by the abrasion resistance test is 5 or less.
[0021] 〔3〕
[0022] The laminated film according to [1] or [2], wherein the pencil hardness is H or higher as determined according to JIS K 5600-5-4:1999.
[0023] 〔4〕
[0024] The laminated film according to any one of [1] to [3], wherein the total light transmittance of the laminated film is 85% or more.
[0025] 〔5〕
[0026] The laminated film according to any one of [1] to [4], wherein the haze of the laminated film is 5% or more and 35% or less.
[0027] 〔6〕
[0028] The laminated film according to any one of [1] to [5], wherein the resin layer comprises microparticles.
[0029] 〔7〕
[0030] According to the laminated film described in [6], the average particle size of the microparticles is 1 μm or more and 16 μm or less.
[0031] 〔8〕
[0032] According to the laminated film of [6] or [7], the difference between the refractive index of the matrix resin contained in the resin layer and the refractive index of the microparticles is 0.00 or more and 0.10 or less.
[0033] 〔9〕
[0034] The laminated film according to any one of [1] to [8], wherein the resin layer comprises nanoparticles with an average particle size of less than 200 nm.
[0035] 〔10〕
[0036] The laminated film according to any one of [1] to [9], wherein the substrate layer is a polyester film.
[0037] 〔11〕
[0038] The laminated film according to any one of [1] to
[10] , wherein the laminated film is a writing feel enhancement film for a touch panel.
[0039] 〔12〕
[0040] A laminated sheet having: a laminated film according to any one of [1] to
[11] ; and a protective film disposed on at least one side of the laminated film.
[0041] 〔13〕
[0042] A laminated sheet having: a laminated film according to any one of [1] to
[11] ; and an adhesive layer disposed on at least one side of the laminated film.
[0043] 〔14〕
[0044] An image display device comprising a laminated film according to any one of [1] to
[11] .
[0045] Invention Effects
[0046] According to this disclosure, it is possible to provide a laminated film with excellent scratch resistance.
[0047] Furthermore, the technical problems and effects of this disclosure are not limited to the contents described above, but include the contents that can be clearly understood by those skilled in the art based on the entire specification. Attached Figure Description
[0048] Figure 1 This is a schematic cross-sectional view showing an example of a laminated film according to the first embodiment of the present disclosure.
[0049] Figure 2 This is a schematic cross-sectional view showing an example of a laminated film according to the first embodiment of the present disclosure.
[0050] Figure 3 This is a cross-sectional schematic diagram illustrating an example of a laminated sheet according to a second embodiment of the present disclosure.
[0051] Figure 4 This is a cross-sectional schematic diagram illustrating an example of a laminated sheet according to a third embodiment of the present disclosure. Detailed Implementation
[0052] The following describes specific embodiments of this disclosure. However, each component and combination thereof in each embodiment is merely an example, and appropriate additions, omissions, substitutions, and other changes may be made to the components without departing from the spirit of this disclosure. This disclosure is not limited to the embodiments.
[0053] Furthermore, the various schemes disclosed in this specification can be combined with any other features disclosed in this specification.
[0054] In this disclosure, the range “X~Y” means “X and below”. Furthermore, when the numerical ranges represented by “X~Y” or “X and below” are described in stages (e.g., in a preferred order), the upper and lower limits of each numerical range can be arbitrarily combined.
[0055] In this disclosure, the phrase "choose one or more of the groups consisting of X, Y, and Z" refers to any one of X, Y, Z, combinations of X and Y, combinations of X and Z, combinations of Y and Z, or combinations of X, Y, and Z.
[0056] In this disclosure, the description of “x1, x2, and x3, etc. X” is used to list x1, x2, and x3, etc. as examples of X, and does not mean that X is limited to x1, x2, and x3, etc.
[0057] 1. Laminated film
[0058] One embodiment of the laminated film disclosed herein includes: a substrate layer; and a resin layer formed on the substrate layer, the opposite side of which has an uneven surface with a concave-convex shape. When the surface shape of the uneven surface is measured using an optical interference surface shape measuring device at a measurement area of 189.46 μm × 252.5 μm, the average area occupancy of the protrusions with a height of 0.3 μm or more is 6% or more. Furthermore, when the uneven surface is subjected to an abrasion resistance test using an abrasion wheel under conditions of a load of 750 g, a sliding distance of 5 cm, a sliding speed of 40 reciprocations / minute, and 100 reciprocations, the laminated film satisfies one or more of the following (a) to (d), preferably all of (a) to (d).
[0059] (a) B1 / A1≥0.80
[0060] (b) B2 / A2 ≥ 0.60
[0061] (c) B3 / A3 ≥ 0.60
[0062] (d) B4 / A4 ≥ 0.60
[0063] (In equations (a) to (d), A1 is the two-dimensional average roughness Ra of the roughness curve elements of the uneven surface before the wear resistance test; B1 is the two-dimensional average roughness Ra of the roughness curve elements of the uneven surface after the wear resistance test; A2 represents the maximum height Rz of the roughness curve element of the uneven surface before the wear resistance test; B2 represents the maximum height Rz of the roughness curve element of the uneven surface after the wear resistance test; A3 represents the average unevenness height Rc of the roughness curve elements of the uneven surface before the wear resistance test; B3 represents the average unevenness height Rc of the roughness curve element of the uneven surface after the wear resistance test; A4 represents the ten-point average roughness Rzjis of the roughness curve elements of the uneven surface before the wear resistance test. B4 represents the ten-point average roughness Rzjis of the roughness curve elements of the uneven surface after the wear resistance test. Figure 1 The diagram shows a cross-sectional view of one embodiment of the laminated film. Figure 1In this laminated film 10, there are: a substrate layer 11; and a resin layer 13 having a textured surface 13a on the side opposite to the substrate layer 11. The laminated film 10 may also have other layers (not shown) described later.
[0064] It should be noted that, in this disclosure, "formed on layer X" includes not only the position directly above layer X (i.e., the position adjacent to layer X), but also the position formed on layer X with any layer in between.
[0065] For the laminated film of this embodiment, by setting the average area occupancy of the protrusions with a height of 0.3 μm or more to a fixed value or more, good scratch resistance can be obtained, and when the laminated film is used as a writing feel enhancement film for touch panel, a good writing feel as when writing on paper with a writing instrument can be achieved.
[0066] In this disclosure, "touch panel" refers to a device that combines a display device such as a liquid crystal panel with a position input device such as a touchpad, and is a device that allows input or device operation by physical contact using a finger or stylus.
[0067] Furthermore, the laminated film of this embodiment satisfies one or more of (a) to (d) above. This means that the protrusions on the surface of the resin layer of the laminated film are not easily worn, and the shape of the protrusions is maintained after the abrasion resistance test. Therefore, when the laminated film of this embodiment is used as a writing feel improvement film for touch panels, the degradation of writing feel caused by repeated input using a stylus can be reduced.
[0068] The laminated film of this embodiment can be used for general applications of films with uneven surfaces, such as waterproof films, anti-glare films, protective films, and writing-feel-enhancing films for touch panels. The laminated film of this embodiment exhibits the aforementioned effects among these applications, and is therefore particularly preferred for use as a writing-feel-enhancing film for touch panels.
[0069] 1-1. Physical properties of laminated films
[0070] 1-1-1. Average area occupancy of protrusions with a height of 0.3 μm or more
[0071] The resin layer has an uneven surface formed by multiple protrusions. The "average area occupancy rate of protrusions with a height of 0.3 μm or more" (hereinafter sometimes simply referred to as "average area occupancy rate of protrusions") mentioned in this disclosure refers to the average area ratio of protrusions with a height of 0.3 μm or more in the uneven surface. The larger the average area occupancy rate of the protrusions on the uneven surface of the resin layer, the more likely the object will climb onto the protrusions when the laminated film is rubbed, for example, by contact with a sharp-tipped object such as a stylus, thus reducing the chance of the object contacting the substrate surface of the film, which is mainly composed of the concave portions of the film. Furthermore, this results in improved scratch resistance of the laminated film.
[0072] The average area occupancy of the convex portion in the uneven surface is typically 6% or more, preferably 7% or more, more preferably 9% or more, and even more preferably 10% or more. There is no particular upper limit to the average area occupancy of the convex portion in the uneven surface, but it is preferably 50% or less, more preferably 30% or less, even more preferably 20% or less, and even more preferably 15% or less. That is, preferred ranges for the average area occupancy of the convex portion in the uneven surface include, for example, 6% or more and 50% or less, 7% or more and 30% or less, 9% or more and 20% or less, and 10% or more and 15% or less.
[0073] By setting the average area occupancy of the protrusions in the uneven surface to above the aforementioned lower limit, the scratch resistance of the laminated film can be improved. By setting the average area occupancy of the protrusions in the uneven surface to below the aforementioned upper limit, when the laminated film is used as a writing feel enhancement film for touch panels, it is easy to achieve a good writing feel similar to writing on paper with a writing instrument.
[0074] The average area occupancy of the protrusions in the uneven surface can be adjusted to the aforementioned range by a method corresponding to the protrusion forming method. For example, the average area occupancy of the protrusions can be adjusted to the aforementioned range by: when forming the protrusions by molding, selecting a mold corresponding to the desired area occupancy of the protrusions; when forming the protrusions by etching, selecting an etching mask having a pattern corresponding to the desired area occupancy of the protrusions; and when forming the protrusions by containing the particles described later in the resin layer, setting the average particle size and content of the particles to the range described later.
[0075] The average area occupancy of the convex portion is determined by measuring the surface shape of the concave and convex surfaces using an optical interferometric surface shape measuring device and performing image processing. The specific method is described below.
[0076] (1) Cut a sample with a size of 6cm×6cm from the laminated film.
[0077] (2) Using an optical interferometric surface shape measuring device (e.g., "VertScan2.0 R3300G Lite" manufactured by Hitachi High-Tech Co., Ltd.), the uneven surface of the resin layer in the sample was measured in 10 fields of view with a measurement area of 189.46 μm × 252.5 μm. At this time, the objective lens magnification was set to 50x. In addition, the sample was placed on the stage with the Y-axis of the measurement aligned with the longitudinal dimension direction of the laminated film (the direction in which the film is wound). The measurement was performed with the sample clamped between two metal frames fitted with rubber pads and the sample loose and curled off.
[0078] (3) Using surface analysis software (e.g., “VS-Viewer” manufactured by Mitsubishi Systems Co., Ltd.), the image obtained in (2) is processed and analyzed under the following conditions to detect protrusions with a height of 0.3 μm or more and to determine their occupied area. The occupied area is divided by the measured area to calculate the area occupancy rate of protrusions with a height of 0.3 μm or more.
[0079] Image processing conditions
[0080] Interpolation processing: Full interpolation (only makes more than 90% of the data valid before interpolation).
[0081] Surface correction: four corrections.
[0082] Analysis conditions
[0083] Analysis type: Breakthrough analysis.
[0084] Height threshold: 0.3μm.
[0085] Reference height: Zero plane (average plane).
[0086] Binarization again: Not performed.
[0087] Particle shaping: Not performed.
[0088] (4) For all 10 fields of view, the area occupancy rate of the convex parts with a height of 0.3 μm or more is calculated by (3), and their average value is set as the average area occupancy rate of the convex parts with a height of 0.3 μm or more.
[0089] However, in (2), since the long dimension direction of the laminated film is unknown, the measurement of 9 fields of view is performed by performing operation X no more than three times instead of the measurement of 10 fields of view. Then, based on the measurement results of these 9 fields of view, (3) and (4) are performed to calculate the average area occupancy of the protrusions with a height of 0.3 μm or more.
[0090] Operation X: After setting the sample and measuring the concave and convex surfaces by making the Y-axis any direction of the sample, rotate the sample 120 degrees and measure the concave and convex surfaces again. Then rotate the sample 120 degrees in the same direction and measure the concave and convex surfaces again.
[0091] Here, if operation X is performed once, the sample is set up with the Y-axis of the sample in any direction. Therefore, this state is maintained to continue with the next operation X. In other words, after setting the sample up with the Y-axis of the sample in any direction and measuring the unevenness, the sample is rotated 120 degrees and the unevenness is measured again. This operation is performed 8 times, measuring a total of 9 fields of view.
[0092] Furthermore, the "zero plane (average plane)" in the setting of the reference height in the analysis conditions is the plane of the "average height (Ave)" obtained by the following formula.
[0093] [Formula 1]
[0094] In the formula, lx is the length of the range along the X-axis in each measured image after image processing.
[0095] ly represents the length of the Y-axis range in each measured image after image processing.
[0096] h(x, y) is the height of each image point (x, y) within the measured image after image processing.
[0097] 1-1-2. Surface roughness of the resin layer
[0098] The surface roughness of the resin layer of the laminated film disclosed herein can be evaluated by selecting one or more of the following: the two-dimensional average roughness Ra (hereinafter, sometimes simply referred to as "two-dimensional average roughness Ra") of the roughness curve element, the maximum height Rz (hereinafter, sometimes simply referred to as "maximum height Rz") of the roughness curve element, the average unevenness height Rc (hereinafter, sometimes simply referred to as "average unevenness height Rc") of the roughness curve element, and the ten-point average roughness Rzjis (hereinafter, sometimes simply referred to as "ten-point average roughness Rzjis") of the roughness curve element.
[0099] The two-dimensional average roughness Ra of the uneven surface is preferably 0.55 μm or more, more preferably 0.60 μm or more, even more preferably 0.70 μm or more, and even more preferably 0.75 μm or more. Furthermore, it is preferably 1.50 μm or less, more preferably 1.30 μm or less, even more preferably 1.20 μm or less, and even more preferably 1.00 μm or less. That is, preferred ranges for the two-dimensional average roughness Ra of the uneven surface include, for example, 0.55 μm or more and 1.50 μm or less, 0.60 μm or more and 1.30 μm or less, 0.70 μm or more and 1.20 μm or less, and 0.75 μm or more and 1.00 μm or less.
[0100] The maximum height Rz of the uneven surface is preferably 4.20 μm or more, more preferably 4.45 μm or more, even more preferably 4.50 μm or more, and even more preferably 5.00 μm or more. Furthermore, it is preferably 7.50 μm or less, more preferably 6.80 μm or less, even more preferably 6.20 μm or less, and even more preferably 5.50 μm or less. That is, preferred ranges for the maximum height Rz of the uneven surface include, for example, 4.20 μm or more and 7.50 μm or less, 4.45 μm or more and 6.80 μm or less, 4.50 μm or more and 6.20 μm or less, and 5.00 μm or more and 5.50 μm or less.
[0101] The average unevenness height Rc of the uneven surface is preferably 3.00 μm or more, more preferably 3.20 μm or more, even more preferably 3.50 μm or more, and preferably 5.20 μm or less, more preferably 4.80 μm or less, even more preferably 4.20 μm or less, and even more preferably 4.00 μm or less. That is, preferred ranges for the average unevenness height Rc of the uneven surface include, for example, 3.00 μm or more and 5.20 μm or less, 3.20 μm or more and 4.80 μm or less, 3.50 μm or more and 4.20 μm or less, and 3.50 μm or more and 4.00 μm or less.
[0102] The ten-point average roughness Rzjis of the uneven surface is preferably 3.00 μm or more, more preferably 3.20 μm or more, even more preferably 3.35 μm or more, and even more preferably 3.70 μm or more. Furthermore, it is preferably 5.30 μm or less, more preferably 4.80 μm or less, even more preferably 4.50 μm or less, and even more preferably 4.00 μm or less. That is, preferred ranges for the ten-point average roughness Rzjis of the uneven surface include, for example, 3.00 μm or more and 5.30 μm or less, 3.20 μm or more and 4.80 μm or less, 3.35 μm or more and 4.50 μm or less, and 3.70 μm or more and 4.00 μm or less.
[0103] Among the two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis of the uneven surface, it is preferable that any one or more of them are within the above range. When using the laminated film as a writing feel enhancement film for touch panel, it is more preferable that all of them are within the above range from the perspective of easily achieving a good writing feel as when writing on paper with a writing instrument.
[0104] The two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis of the uneven surface can be adjusted to the above ranges by a method corresponding to the method of forming the protrusion. For example, the two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis can be adjusted to the above ranges by: when forming the protrusion by molding, selecting a mold corresponding to the desired surface roughness; when forming the protrusion by etching, selecting an etching mask having a pattern corresponding to the desired surface roughness; and when forming the protrusion by containing the particles described later in the resin layer, setting the average particle size and content of the particles to the ranges described later.
[0105] The two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis of the uneven surface are measured using a surface roughness measuring instrument (e.g., SURFCOM 1400G-12, Tokyo Seimitsu Co., Ltd.) under the following conditions, in accordance with JIS B 0601:2013 (Geometrical Specifications of Products (GPS) - Surface Properties: Profile Curve Method - Terms, Definitions and Surface Property Parameters, amended March 21, 2013).
[0106] Surface roughness measurement conditions
[0107] Measurement length: 10mm.
[0108] Measurement speed: 0.3 mm / second.
[0109] Cutoff wavelength (λc): 0.8 mm.
[0110] Radius of the probe tip: 2μm.
[0111] Cone angle: 90°.
[0112] 1-1-3. Wear resistance
[0113] The laminated film of this embodiment satisfies one or more of the above (a) to (d) when undergoing abrasion resistance testing.
[0114] (a) Related to the ratio (B1 / A1) of the two-dimensional average roughness Ra of the uneven surface after the wear resistance test to the two-dimensional average roughness Ra of the uneven surface before the wear resistance test, it is typically 0.80 or more, preferably 0.90 or more, more preferably 0.95 or more, and even more preferably 0.99 or more. There is no particular upper limit to B1 / A1, but it is preferably 1.00 or less. That is, preferred ranges for B1 / A1 include, for example, 0.80 or more and 1.00 or less, 0.90 or more and 1.00 or less, 0.95 or more and 1.00 or less, and 0.99 or more and 1.00 or less.
[0115] (b) The ratio (B2 / A2) of the maximum height Rz of the uneven surface after the abrasion test to the maximum height Rz of the uneven surface before the abrasion test is typically 0.60 or more, preferably 0.70 or more, more preferably 0.75 or more, and even more preferably 0.77 or more. There is no particular upper limit to B2 / A2, but it is preferably 1.00 or less, 0.90 or less, or 0.80 or less. That is, preferred ranges for B2 / A2 include, for example, 0.60 or more and 1.00 or less, 0.70 or more and 1.00 or less, 0.75 or more and 0.90 or less, and 0.77 or more and 0.80 or less.
[0116] (c) The ratio (B3 / A3) of the average unevenness height Rc of the uneven surface after the abrasion test to the average unevenness height Rc of the uneven surface before the abrasion test is typically 0.60 or more, preferably 0.70 or more, more preferably 0.74 or more, further preferably 0.80 or more, and even more preferably 0.84 or more. The upper limit of B3 / A3 is not particularly limited, but is preferably 1.00 or less, 0.95 or less, or 0.90 or less. That is, preferred ranges for B2 / A2 include, for example, 0.60 or more and 1.00 or less, 0.70 or more and 1.00 or less, 0.74 or more and 0.95 or less, 0.80 or more and 0.95 or less, and 0.84 or more and 0.90 or less.
[0117] (d) The ratio (B4 / A4) of the ten-point average roughness Rzjis of the uneven surface after the wear resistance test to the ten-point average roughness Rzjis of the uneven surface before the wear resistance test is typically 0.60 or more, preferably 0.70 or more, more preferably 0.74 or more, further preferably 0.80 or more, and even more preferably 0.84 or more. The upper limit of B3 / A3 is not particularly limited, but is preferably 1.00 or less, 0.95 or less, or 0.90 or less. That is, preferred ranges for B4 / A4 include, for example, 0.60 or more and 1.00 or less, 0.70 or more and 1.00 or less, 0.74 or more and 0.95 or less, 0.80 or more and 0.95 or less, and 0.84 or more and 0.90 or less.
[0118] When friction is applied to a surface with an uneven shape, the protrusions are removed, thus significantly reducing the two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis. In contrast, the protrusions of the uneven surface of the laminated film of this embodiment are less prone to wear, and the shape of the protrusions does not change significantly after friction is applied in an abrasion resistance test. Therefore, in the laminated film of this embodiment, the reduction in two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis caused by friction is suppressed, and B1 / A1, B2 / A2, B3 / A3, and B4 / A4 exhibit values above a certain level. Furthermore, as a result, the laminated film of this embodiment exhibits excellent scratch resistance, and when used as a writing feel enhancement film for touch panels, the writing feel is not easily degraded even with repeated stylus input, maintaining a good writing feel similar to writing on paper with a writing instrument.
[0119] The laminated film of this embodiment satisfies one or more of (a) to (d). From the perspective of improving the continuity of writing feel when used as a film for improving writing feel in a touch panel, it is preferable to satisfy two or more of (a) to (d), more preferably to satisfy three or more of (a) to (d), and even more preferably to satisfy all of (a) to (d). Furthermore, in these general and preferred solutions, (a) to (d) are preferably B1 / A1, B2 / A2, B3 / A3, and B4 / A4, respectively, which are the preferred ranges described above.
[0120] As a method for forming the uneven surface of the resin layer to satisfy (a) to (d) the manner, in addition to adjusting the average area occupancy of the protrusions to the range described above, other methods may include: selecting a resin with high hardness, such as (meth)acrylic resin and its crosslinking products, as the constituent material of the resin layer; making the resin layer contain nanoparticles as described later; when making the resin layer contain microparticles as described later, selecting microparticles of a material with high hardness, such as (meth)acrylic resin and its crosslinking products, as microparticles; etc.
[0121] It should be noted that, in this disclosure, "(meth)acrylic resin" refers to either or both of acrylic resin and methacrylic resin. Similarly, "(meth)acrylate" refers to either or both of acrylic ester and methacrylate.
[0122] The above-mentioned abrasion resistance test was conducted on the uneven surface of the resin layer of the laminated film under the conditions of a load of 750g, a sliding distance (single stroke, linear sliding) of 5cm, a sliding speed of 40 reciprocating strokes / minute, and 100 reciprocating strokes.
[0123] The scratch resistance of the laminated film in this embodiment can also be evaluated based on the number of visually perceptible scratches produced by the abrasion resistance test described above. The fewer the number of visually perceptible scratches produced by the abrasion resistance test, the better the scratch resistance of the laminated film is considered to be. Preferably, there are 5 or fewer scratches, more preferably 3 or fewer, and even more preferably 0 scratches.
[0124] In this disclosure, "visible scars" refers to scars with a width of 0.1 mm or more and a length of 1.0 mm or more.
[0125] 1-1-4. Pencil Hardness
[0126] The laminated film of this embodiment is expected to be used in applications requiring scratch resistance, such as writing feel enhancement films for touch panels, and therefore preferably has sufficient pencil hardness. Specifically, the pencil hardness of the laminated film of this embodiment is preferably H or higher, more preferably 2H or higher, and even more preferably 3H or higher. With the pencil hardness of the laminated film within the above range, it can also function as a protective film for image display devices such as touch panels. The upper limit of the pencil hardness of the laminated film of this embodiment is not particularly limited, but it is generally 10H or lower, and may also be 9H or lower, or 7H or lower. That is, preferred ranges for the pencil hardness of the laminated film include, for example, H or higher and 10H or lower, 2H or higher and 9H or lower, and 3H or higher and 7H or lower.
[0127] As a method for setting the pencil hardness of the laminated film to the above-mentioned range, examples include: selecting a resin with high hardness, such as (meth)acrylic resin and its crosslinking products, as the constituent material of the resin layer; making the resin layer contain nanoparticles as described later; when making the resin layer contain the microparticles as described later, selecting microparticles of a material with high hardness, such as (meth)acrylic resin and its crosslinking products, as microparticles; etc.
[0128] For the pencil hardness of the laminated film, it was determined according to JIS K 5600-5-4:1999 (General Test Methods for Coatings - Part 5: Mechanical Properties of Coatings - Section 4: Scratch Hardness (Pencil Method), established on April 20, 1999), using a pencil scratch hardness tester (e.g., "No. 553-M" manufactured by Yasuda Seiki Co., Ltd.). The test was conducted on the resin layer of the laminated film under the conditions of a load of 750g, a test speed of 30mm / min, and a test distance of 15mm.
[0129] 1-1-5. Haze
[0130] From the perspective of achieving anti-glare properties, the haze of the laminated film in this embodiment is preferably 5% or more, more preferably 10% or more, further preferably 14% or more, and even more preferably 15% or more. On the other hand, from the viewpoint of ensuring transparency suitable for optical applications such as writing feel improvement films for touch panels, the upper limit of the haze of the laminated film is preferably 50% or less, more preferably 40% or less, further preferably 35% or less, and even more preferably 30% or less. That is, as preferred ranges for the haze of the laminated film, for example, ranges of 5% or more and 50% or less, 10% or more and 40% or less, 14% or more and 35% or less, and 15% or more and 30% or less can be listed.
[0131] The haze of the laminated film was measured using a haze meter (e.g., "HM-150L2N" manufactured by Murakami Color Technology Research Institute Co., Ltd.) in accordance with JIS K 7136:2000 (Method for determining haze of transparent plastics, adopted on February 20, 2000). In this case, the uneven surface of the resin layer was designated as the incident light surface.
[0132] 1-1-6. Total transmittance
[0133] From the viewpoint of ensuring transparency suitable for optical applications such as writing feel enhancement films for touch panels, the total light transmittance of the laminated film in this embodiment is preferably 80% or more, more preferably 85% or more, further preferably 90% or more, and even more preferably 95% or more. On the other hand, there is no particular upper limit to the total light transmittance of the laminated film, and it is generally 100% or less. That is, as a preferred range for the total light transmittance of the laminated film, for example, ranges of 80% or more and 100% or less, 85% or more and 100% or less, 90% or more and 100% or less, and 95% or 100% or less can be listed.
[0134] The total transmittance of the laminated film was measured using a haze meter (e.g., "HM-150L2N" manufactured by Murakami Color Technology Research Institute Co., Ltd.) according to JIS K 7361-1:1997 (Plastics - Test method for total transmittance of transparent materials - Part 1: Single beam method, established January 20, 1997). In this case, the uneven surface of the resin layer was designated as the incident light surface.
[0135] 1-2. Substrate layer
[0136] The substrate layer is not particularly limited and can be appropriately selected according to the intended use of the laminated film. For example, plastic films and glass plates can be listed as substrate layers. Considering the affinity with the resin layer and the high interlayer adhesion, plastic films are preferred. The substrate layer can have a single-layer structure or a multi-layer structure.
[0137] Examples of plastic films include, for example, polyester films such as polyethylene terephthalate films, polybutylene terephthalate films, and polyethylene naphthalate films; polyolefin films such as polyethylene films, polypropylene films, and polymethylpentene films; cellulose-based films such as cellophane, diacetyl cellulose films, triacetyl cellulose films, and acetyl cellulose butyrate films; vinyl resin films such as polyvinyl chloride films, polyvinylidene chloride films, polyvinyl alcohol films, ethylene-vinyl acetate copolymer films, and polystyrene films; polycarbonate films; polysulfone films; polyetheretherketone films; polyethersulfone films; polyetherimide films; fluoropolymer films; polyamide films; (meth)acrylic resin films; polyurethane resin films; cyclic olefin polymer films such as norbornene polymer films; and cyclic conjugated diene polymer films; etc. These plastic films can also be laminated in two or more layers as a substrate layer.
[0138] Among these plastic films, polyester film is preferred as the substrate layer, and polyethylene terephthalate film is more preferred, considering both transparency and high strength.
[0139] To improve interlayer adhesion with adjacent layers, the substrate layer can also undergo any surface treatment. Examples of surface treatment methods include corona treatment, flame treatment, UV ozone treatment, chromic acid treatment, and sandblasting.
[0140] The thickness of the substrate layer is not particularly limited, but it is preferably 25 μm or more, more preferably 55 μm or more, and even more preferably 75 μm or more. Furthermore, it is preferably 200 μm or less, more preferably 125 μm or less, and even more preferably 100 μm or less. That is, preferred ranges for the substrate layer include, for example, 25 μm or more and 200 μm or less, 55 μm or more and 125 μm or less, and 75 μm or more and 100 μm or less.
[0141] By setting the thickness of the substrate layer to the lower limit or above, the aforementioned pencil hardness is easily achieved. When the laminated film is used as a writing feel enhancement film for touch panels, the impact of the adhesive used to adhere it to the touch panel on the writing feel and the hardness of the touch panel surface can be reduced. Furthermore, by setting the thickness of the substrate layer to the upper limit or below, appropriate flexibility can be obtained, thus improving the ease of processing the laminated film of this embodiment.
[0142] 1-3. Resin layer
[0143] The resin layer is a layer formed on the substrate layer, and has an uneven surface on the side opposite to the substrate layer. The uneven surface of the resin layer is the contact surface with the stylus when the laminated film of this embodiment is used as a writing feel enhancement film for a touch panel. Therefore, it is preferred to form the outermost surface of the laminated film. Thus, it is preferable that no layer is formed on the surface of the resin layer opposite to the substrate layer.
[0144] There are no particular limitations on the method of forming the resin layer as long as the desired uneven surface can be formed. For example, the following methods can be listed: after forming a resin layer without uneven surface on the substrate layer by extrusion molding, coating or the like, an uneven shape is formed on the side of the resin layer opposite to the substrate layer by molding and etching or the like; and as shown in the examples described later, a coating composition containing particles having a shape corresponding to the protrusion is coated on the substrate layer.
[0145] The materials constituting the resin layer are not particularly limited. They can be the matrix resin alone, or a composition that includes any components other than the matrix resin, such as the microparticles and nanoparticles described later.
[0146] The matrix resin contained in the resin layer is preferably a polymer of a polyfunctional monomer having two or more but no more than eight polymerizable groups, and more preferably a polymer of a polyfunctional (meth)acrylate having two or more but no more than eight (meth)acryloyl groups. The matrix resin can be a homopolymer or a copolymer formed by copolymerizing any two or more monomers in any ratio.
[0147] Examples of multifunctional (meth)acrylates include: ethylene glycol dimethacrylate, propylene glycol dimethacrylate, butanediol dimethacrylate, neopentyl glycol dimethacrylate, and hexanediol dimethacrylate, among other alkylene glycol dimethacrylates; diethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, and polyoxytetramethylene glycol dimethacrylate, among other polyoxyalkylene glycol dimethacrylates; tricyclodecanediethanol dimethacrylate, adamantane dimethacrylate, etc. Di(meth)acrylates having a bridged ring hydrocarbon group, such as methacrylates; tri(meth)acrylates such as glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and ethoxytrimethylolpropane tri(meth)acrylate; tetra(meth)acrylates such as pentaerythritol tetra(meth)acrylate; penta(meth)acrylates such as dipentaerythritol penta(meth)acrylate; and hexa(meth)acrylates such as dipentaerythritol hexa(meth)acrylate; etc. Among them, as a polyfunctional (meth)acrylate, one or more are preferably selected from the group consisting of dipentaerythritol hexa(meth)acrylate and ethoxytrimethylolpropane tri(meth)acrylate.
[0148] The resin layer preferably contains microparticles. Here... Figure 2 The diagram shows a cross-sectional schematic of one embodiment of a laminated film having a resin layer containing microparticles. Figure 2 In the laminated film 10 shown, the microparticles 13b are held in the resin layer 13 by being dispersed in the resin layer 13, and while covered by the resin material 13c, a portion of them protrudes from the side of the resin layer 13 opposite to the substrate layer 11, thereby forming a protrusion 13d that reflects the shape of the microparticles 13b. Furthermore, a concave-convex surface 13a is formed by a plurality of protrusions 13d.
[0149] From the viewpoint of forming a surface with the aforementioned two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis, the average particle size is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 6 μm or more, and preferably 16 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less. That is, preferred ranges for the average particle size include, for example, 1 μm or more and 16 μm or less, 3 μm or more and 12 μm or less, and 6 μm or more and 10 μm or less.
[0150] In this disclosure, "average particle size" refers to the median particle size (D). 50 The particle size distribution was measured using a laser diffraction scattering particle size distribution measuring device.
[0151] The shape of the microparticles is not particularly limited, but spherical is preferred. In this disclosure, spherical does not only refer to perfect spheres, but also includes shapes with a circular, substantially circular, elliptical, or substantially elliptical cross-sectional shape, such as elongated spheres and oblate spheroids. However, the microparticles contained in the resin layer are preferably perfect spheres or substantially perfect spheres. This is because the shape of the microparticles reflects the shape of the protrusions. Therefore, if the microparticles are perfect spheres or substantially perfect spheres, they can disperse the impact and reduce abrasion when subjected to impact by contact with a sharp-tipped object such as a stylus pen. As a result, the abrasion resistance of the laminated film can be improved.
[0152] Examples of materials constituting the microparticles include (meth)acrylic resins, melamine resins, acrylic-styrene copolymers, polycarbonate resins, polyethylene resins, polystyrene resins, and benzoguanamine resins, as well as their crosslinked products. From the perspective of excellent transparency and strength, the microparticles are preferably (meth)acrylic resin particles, more preferably crosslinked (meth)acrylic resin particles, and even more preferably crosslinked polymethyl methacrylate particles (e.g., the "Techpolymer SSX series" manufactured by Sekisui Chemicals Co., Ltd.).
[0153] When the resin layer contains microparticles, the content of microparticles in the resin layer relative to 100 parts by mass of the matrix resin is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more. Furthermore, it is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less. That is, when the resin layer contains microparticles, the preferred ranges for the content of microparticles in the resin layer relative to 100 parts by mass of the matrix resin include, for example, 1 part by mass and less than 20 parts by mass, 2 parts by mass and less than 15 parts by mass, 3 parts by mass and less than 10 parts by mass, and 4 parts by mass and less than 5 parts by mass.
[0154] By setting the content of microparticles in the resin layer to the above range, it is easy to adjust the two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, ten-point average roughness Rzjis, and average area occupancy of the protrusions of the uneven surface to the above preferred range.
[0155] The refractive index of the microparticles is preferably the same as or approximately the same as that of the matrix resin. More specifically, the difference between the refractive index of the matrix resin and the refractive index of the microparticles is preferably 0.10 or less, more preferably 0.05 or less, even more preferably 0.03 or less, and generally 0.00 or more. That is, preferred ranges for the difference between the refractive index of the matrix resin and the refractive index of the microparticles include, for example, 0.00 or more and 0.10 or less, 0.00 or more and 0.05 or less, and 0.00 or more and 0.03 or less.
[0156] By setting the difference between the refractive index of the matrix resin and the refractive index of the microparticles within the aforementioned range, a laminated film with low haze can be obtained.
[0157] The resin layer preferably contains nanoparticles with an average particle size of less than 200 nm (hereinafter, sometimes simply referred to as "nanoparticles").
[0158] The average particle size of the nanoparticles is typically below 200 nm, preferably below 100 nm, more preferably below 50 nm, and even more preferably below 30 nm. The lower limit of the average particle size is not particularly limited, but it is preferably above 1 nm, more preferably above 5 nm, even more preferably above 10 nm, and even more preferably above 15 nm. That is, preferred ranges for the average particle size of the nanoparticles include, for example, ranges of 1 nm and above and below 200 nm, 5 nm and above and below 100 nm, 10 nm and above and below 50 nm, and 15 nm and above and below 30 nm.
[0159] By incorporating nanoparticles of this size into the resin layer, the abrasion resistance of the uneven surface of the resin layer is improved, resulting in enhanced scratch resistance of the laminated film.
[0160] Examples of nanoparticles include silica nanoparticles and alumina particles. From the viewpoint of improving the wear resistance of the uneven surface of the resin layer, silica nanoparticles are preferred.
[0161] When the resin layer contains nanoparticles, the content of nanoparticles in the resin layer relative to 100 parts by mass of the matrix resin is preferably 5 parts by mass or more, more preferably 8 parts by mass or more, even more preferably 10 parts by mass or more, and preferably 40 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less. That is, when the resin layer contains nanoparticles, the preferred ranges for the content of nanoparticles in the resin layer relative to 100 parts by mass of the matrix resin include, for example, 5 parts by mass or more and 40 parts by mass or less, 8 parts by mass or more and 30 parts by mass or less, and 10 parts by mass or more and 20 parts by mass or less.
[0162] By setting the content of nanoparticles in the resin layer within the aforementioned range, the influence of nanoparticles on the two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis of the uneven surface can be suppressed. Furthermore, the transparency and ease of formation of the resin layer can be ensured, and the laminated film can satisfy one or more of the above (a) to (d) or have its pencil hardness increased. As a result, a laminated film with excellent scratch resistance can be obtained.
[0163] The thickness of the resin layer is not particularly limited, but it is preferably 2 μm or more, more preferably 3 μm or more, and even more preferably 4 μm or more. Furthermore, it is preferably 7 μm or less, more preferably 6 μm or less, and even more preferably 5 μm or less. That is, as preferred ranges for the thickness of the resin layer, for example, ranges of 2 μm or more and 7 μm or less, 3 μm or more and 6 μm or less, and 4 μm or more and 5 μm or less can be listed.
[0164] By setting the resin layer thickness above the aforementioned lower limit, sufficient pencil hardness can be imparted to the laminated film. By setting the resin layer thickness below the aforementioned upper limit, sufficient haze can be ensured, resulting in anti-glare properties. Furthermore, especially when forming protrusions by containing microparticles in the resin layer, by setting the resin layer thickness below the aforementioned upper limit, the microparticles are less likely to be embedded within the resin layer, forming protrusions that reflect the shape of the microparticles. Therefore, when this laminated film is used as a writing feel enhancement film for touch panels, it is easy to achieve a good writing feel similar to writing on paper with a writing instrument.
[0165] It should be noted that, in this disclosure, "the thickness of the resin layer" refers to the distance between the side of the resin layer opposite to the uneven surface and the aforementioned zero surface (average surface). "The thickness of the resin layer" does not include the thickness of layers other than the resin layer, such as the substrate layer and other layers described later.
[0166] Without impairing the effects of this disclosure, the resin layer may also contain any additives. Examples of such additives include fluorinated antifouling additives, photopolymerization initiators, ultraviolet absorbers, antioxidants, light stabilizers, antistatic agents, silane coupling agents, anti-aging agents, heat-resistant polymerization inhibitors, surfactants, preservation stabilizers, plasticizers, lubricants, defoamers, wetting modifiers, and coating modifiers. When the resin layer contains any additives, the amount added is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and even more preferably 1 part by weight or less, and usually more than 0 parts by weight, relative to 100 parts by weight of the base resin.
[0167] 1-4. Other layers
[0168] Without impairing the effects of this disclosure, the laminated film of this embodiment may also have other layers besides those described above. Examples of other layers include, for instance, a primer layer for improving the adhesion between the substrate layer and the resin layer.
[0169] 2. Laminated sheets with protective film
[0170] The second embodiment of this disclosure is a laminated sheet having: the laminated film of the first embodiment; and a protective film disposed on one or both sides of the laminated film.
[0171] As a protective film, there are no particular limitations; examples include polyester films such as polyethylene terephthalate films; polyolefin films such as polyethylene films; and thermoplastic polyurethane elastomer films; and other plastic films.
[0172] To improve the adhesion between the protective film and the laminated film, the protective film may also have an adhesive layer on one side. Examples of materials that constitute the adhesive layer of the protective film include ethylene-vinyl alcohol, (meth)acrylic resin, and silicone resin. Therefore, more specifically, a multilayer film having a polyethylene film and an adhesive layer containing ethylene-vinyl alcohol can be cited.
[0173] The thickness of the protective film is not particularly limited, but it is preferably 30 μm or more and 125 μm or less, and more preferably 30 μm or more and 80 μm or less.
[0174] Figure 3 The diagram shows a cross-sectional view of one embodiment of the laminated sheet. Figure 3 In this laminate 20, there is a laminated film 10 and protective films 21 disposed on both sides of the laminated film 10. The laminated film 10 has a substrate layer 11 and a resin layer 13 with a textured surface 13a opposite to the substrate layer 11. Furthermore, the protective film 21 has a protective film substrate layer 21a and an adhesive layer 21b. One protective film 21 is adhered to the laminated film 10 such that the adhesive layer 21b is in contact with the textured surface 13a of the laminated film 10. The other protective film 21 is adhered to the laminated film 10 such that the adhesive layer 21b is in contact with the side of the substrate layer 11 opposite to the resin layer 13.
[0175] A laminated sheet is formed by depositing a protective film on one or both sides of the laminated film, thereby protecting the laminated film from damage such as friction and abrasion. From the viewpoint of suppressing wear on the protrusions of the resin layer of the laminated film before use (e.g., during the flow stage), the protective film is preferably disposed on at least the uneven surfaces of the laminated film.
[0176] 3. Laminated sheets with adhesive
[0177] The third embodiment of this disclosure is a laminated sheet having: the laminated film of the first embodiment; and an adhesive layer disposed on one or both sides of the laminated film.
[0178] Materials used as adhesive layers include, for example, (meth)acrylic resin and epoxy resin.
[0179] The thickness of the adhesive is not particularly limited, but it is preferably 25 μm or more and 100 μm or less, more preferably 25 μm or more and 50 μm or less.
[0180] Figure 4 The diagram shows a cross-sectional view of one embodiment of the laminated sheet. Figure 4In this laminate 20, there is a laminated film 10 and an adhesive layer 23 disposed on one side of the laminated film 10. The laminated film 10 has a substrate layer 11 and a resin layer 13 with a concave-convex surface 13a opposite to the substrate layer 11. Furthermore, the adhesive layer 23 is bonded to the laminated film 10 in such a way that it is in contact with the side of the substrate layer 11 opposite to the resin layer 13.
[0181] A laminated sheet is formed by providing an adhesive layer on one or both sides of the laminated film, thereby facilitating the adhesion of the laminated film to image display devices and the like. For ease of use when the laminated film is used as an anti-glare film or a writing feel-enhancing film for touch panels, the adhesive layer is preferably disposed on the side of the substrate layer 11 opposite to the resin layer 13. Furthermore, the laminated sheet of this embodiment also preferably has a release liner disposed on the adhesive layer, which is formed by performing a release treatment on plastic films or paper based on silicone resin or the like.
[0182] 4. Image display device
[0183] The third embodiment of this disclosure is an image display device incorporating the laminated film of the first embodiment. There are no particular limitations on the image display device; examples include liquid crystal displays, organic electroluminescent (organic EL) displays, electronic paper, electronic notebooks (also called digital notebooks or electronic notepads), and electronic blackboards. When these image display devices are touch panels, as described above, the laminated film of the first embodiment functions as a writing feel-enhancing film, maintaining a good writing feel similar to writing on paper with a writing instrument for a long time due to its excellent scratch resistance, and is therefore preferred. Electronic paper and electronic notebooks (also called digital notebooks or electronic notepads) are particularly preferred as touch panel-type image display devices.
[0184] In this embodiment, the image display device preferably has the laminated film of the first embodiment adhered directly to or through an adhesive layer on the display surface of the image display device. Alternatively, the image display device may adhere the laminated film to the display surface through the adhesive layer of the laminated sheet of the third embodiment.
[0185] Example
[0186] The present disclosure will be further described in detail below through embodiments. The present disclosure is not limited to the following embodiments as long as it does not depart from its spirit.
[0187] [Reagents]
[0188] The materials used in the coating composition for forming the resin layer are described below.
[0189] DPHA: dipentaerythritol hexaacrylate, manufactured by Daicel-Allnex Co., Ltd.
[0190] AU-230: Silicone-based UV-curable anti-glare coating agent, manufactured by TOKUSHIKI Co., Ltd.
[0191] AS-201S: Silicone-based UV-curable hard coating, manufactured by TOKUSHIKI Co., Ltd.
[0192] CAP: Cellulose acetate propionate.
[0193] BYK 3519: Silica Nanoparticle Dispersion (Silica nanoparticle content: 40% by mass, average particle size of silica nanoparticles: 20 nm, solvent: ethoxytrimethylolpropane triacrylate), manufactured by BYK Corporation.
[0194] Omnirad 127: Photopolymerization initiator, manufactured by IGM Resins BV.
[0195] Techpolymer SSX-108: Crosslinked polymethyl methacrylate orthospherical microparticles (average particle size: 8 μm, refractive index: 1.49), manufactured by Sekisui Chemicals Co., Ltd.
[0196] Techpolymer SSX-115HXE: Crosslinked polymethyl methacrylate orthospherical microparticles (average particle size: 15 μm, refractive index: 1.49), manufactured by Sekisui Chemicals Co., Ltd.
[0197] KY1203: Fluorine-based antifouling additive (active ingredient concentration: 20% by mass), manufactured by Shin-Etsu Chemical Industry Co., Ltd.
[0198] MEK: Methyl ethyl ketone.
[0199] 1-BuOH: 1-Butanol.
[0200] PGM: Propylene glycol monomethyl ether.
[0201] [Evaluation Method]
[0202] (Haze)
[0203] According to JIS K 7136:2000 (Method for determining haze of plastics—transparent materials, established on February 20, 2000), the haze of the laminated film was measured using a haze meter ("HM-150L2N" manufactured by Murakami Color Technology Research Institute Co., Ltd.). At this time, the uneven surface of the resin layer was set as the light-incident surface.
[0204] (Total transmittance)
[0205] According to JIS K 7361-1:1997 (Plastics - Test method for total light transmittance of transparent materials - Part 1: Single beam method, established January 20, 1997), the total light transmittance of the laminated film was determined using a haze meter (Murakami Color Technology Research Institute Co., Ltd. "HM-150L2N"). In this case, the uneven surface of the resin layer was designated as the incident light surface.
[0206] (Average area occupancy of the convex portion)
[0207] Using an optical interferometric surface shape measuring apparatus (VertScan2.0R3300G Lite, Hitachi High-Tech, Inc.), the uneven surface of the resin layer in a 6cm × 6cm sample cut from a laminated film was measured in 10 fields of view at a measurement area of 189.46μm × 252.5μm. The objective lens magnification was set to 50x. Furthermore, the sample was clamped between two metal frames with the Y-axis aligned with the longitudinal dimension of the laminated film, and looseness and curling were removed before being placed on the stage.
[0208] By using surface analysis software (VS-Viewer manufactured by Mitsubishi Kagami Systems Co., Ltd.) for image processing and analysis, protrusions with a height of 0.3 μm or more were detected, and their occupied area was calculated. This occupied area was divided by the measured area to calculate the area occupancy rate of the protrusions. The area occupancy rate of the protrusions was calculated for all 10 fields of view, and their average value was taken as the average area occupancy rate of the protrusions.
[0209] Image processing conditions
[0210] Interpolation processing: Full interpolation (only makes more than 90% of the data valid before interpolation).
[0211] Surface correction: four corrections.
[0212] Analysis conditions
[0213] Analysis type: Breakthrough analysis.
[0214] Height threshold setting: 0.3μm.
[0215] Reference height: Zero plane (average plane).
[0216] Binarization again: Not performed.
[0217] Particle shaping: Not performed.
[0218] (Pencil hardness)
[0219] According to JIS K 5600-5-4:1999 (General Test Methods for Coatings - Part 5: Mechanical Properties of Coatings - Section 4: Scratch Hardness (Pencil Test), established on April 20, 1999), the pencil hardness of laminated films was determined using a pencil scratch hardness tester (No. 553-M, Yasuda Seiki Co., Ltd.). The test was conducted on the resin layer of the laminated film under the conditions of a load of 750g, a test speed of 30mm / min, and a test distance of 15mm.
[0220] (Number of scratches after abrasion resistance test)
[0221] Abrasion resistance tests were conducted on the uneven surface of the resin layer of the laminated film using a TABER abrasion wheel (Daitron Corporation "CS-10") under the conditions of a load of 750g, a sliding distance (single stroke, linear sliding) of 5cm, a sliding speed of 40 reciprocations / minute, and 100 reciprocations.
[0222] After the abrasion resistance test, observe the resin layer of the laminated film and count the number of visible scratches.
[0223] (Sensory of writing)
[0224] Eight trained judges used a Nintendo DS (registered trademark) stylus to evaluate the writing feel of the resin surface, judging according to the following criteria.
[0225] Evaluation Criteria
[0226] A: At least five judges felt that the writing experience was similar to that of writing on paper with a pencil.
[0227] B: Fewer than four judges felt that the writing experience was similar to that of writing on paper with a pencil.
[0228] (Surface roughness of the resin layer)
[0229] The two-dimensional average roughness Ra, maximum height Rz, average unevenness height Rc, and ten-point average roughness Rzjis of the resin layer's uneven surface were measured under the following conditions using a surface roughness measuring instrument (SURFCOM 1400G-12, Tokyo Seimitsu Co., Ltd.) in accordance with JIS B 0601:2013 (Geometric Specifications of Products (GPS) - Surface Properties: Profile Curve Method - Terms, Definitions and Surface Property Parameters, revised March 21, 2013).
[0230] Surface roughness measurement conditions
[0231] Measurement length: 10mm.
[0232] Measurement speed: 0.3 mm / second.
[0233] Cutoff wavelength (λc): 0.8 mm.
[0234] Radius of the probe tip: 2μm.
[0235] Cone angle: 90°.
[0236] [Example 1]
[0237] The components listed in Table 1 are mixed to obtain the coating composition.
[0238] The coating composition was applied to a polyethylene terephthalate film (Mitsubishi Chemical Corporation "O321E75", thickness: 75 μm) using a wire rod, and then heat-treated in an oven at a temperature between 80°C and 100°C to obtain a dried coating film. Next, the dried coating film was irradiated with 500 mJ / cm² using an ultraviolet irradiation device (USHIO Electric Corporation). 3 Ultraviolet light was used to fabricate a laminated film. The resulting laminated film was evaluated for various physical properties. The results are shown in Tables 2 and 3.
[0239] [Examples 2-3, Comparative Examples 1-3]
[0240] The composition of the coating composition was changed as described in Table 1. Otherwise, a laminated film was prepared in the same manner as in Example 1, and various physical properties were evaluated. The results are shown in Tables 2 and 3.
[0241] [Table 1]
[0242] [Table 2]
[0243] The difference between the refractive index of the matrix resin and the refractive index of the particles.
[0244] [Table 3]
[0245] Countless wounds were confirmed.
[0246] According to Examples 1-3, by setting the average area occupancy of the protrusions in the resin layer to 6% or more, B1 / A1 to 0.8 or more, B2 / A2 to 0.6 or more, B3 / A3 to 0.6 or more, and B4 / A4 to 0.6 or more, it is shown that the protrusions on the uneven surface of the resin layer of the laminated film are less prone to wear. Therefore, it can be seen that by setting the average area occupancy of the protrusions in the resin layer of the laminated film to 6% or more, scratch resistance can be improved.
[0247] Explanation of reference numerals in the attached figures
[0248] 10: Laminated film; 11: Substrate layer; 13: Resin layer; 13a: Concave-convex surface; 13b: Particle; 13c: Resin material; 13d: convex part; 20: Laminated sheets; 21: Protective film; 21a: Protective film substrate layer; 21b: Adhesive layer; 23: Adhesive layer.
Claims
1. A laminated film having: A substrate layer; and a resin layer formed on the substrate layer, the opposite side of which has a surface with an uneven shape. When measuring the surface shape of the uneven surface using an optical interferometric surface shape measuring device with a measurement area of 189.46 μm × 252.5 μm, the average area occupancy of the protrusions with a height of 0.3 μm or more is 6% or more. When the wear resistance test is conducted on the uneven surface using a wear wheel under the conditions of a load of 750g, a sliding distance of 5cm, a sliding speed of 40 reciprocations / minute, and 100 reciprocations, the laminated film satisfies one or more of the following (a) to (d). (a) B1 / A1 ≥ 0.80, (b) B2 / A2 ≥ 0.60, (c) B3 / A3 ≥ 0.60, (d) B4 / A4 ≥ 0.60, In equations (a) to (d), A1 is the two-dimensional average roughness Ra of the roughness curve elements of the uneven surface before the wear resistance test. B1 is the two-dimensional average roughness Ra of the roughness curve elements of the uneven surface after the wear resistance test; A2 is the maximum height Rz of the roughness curve element of the uneven surface before the wear resistance test; B2 is the maximum height Rz of the roughness curve element of the uneven surface after the wear resistance test; A3 represents the average unevenness height Rc of the roughness curve elements of the uneven surface before the wear resistance test; B3 is the average unevenness height Rc of the roughness curve element of the uneven surface after the wear resistance test; A4 represents the ten-point average roughness Rzjis of the roughness curve elements of the uneven surface before the wear resistance test. B4 is the ten-point average roughness Rzjis of the roughness curve elements of the uneven surface after the wear resistance test.
2. The laminated film according to claim 1, wherein, The number of scratches with a width of 0.1 mm or more and a length of 1.0 mm or more produced by the wear resistance test is 5 or less.
3. The laminated film according to claim 1, wherein, The pencil hardness is H or higher, as determined by JIS K 5600-5-4:1999.
4. The laminated film according to claim 1, wherein, The total light transmittance of the laminated film is above 85%.
5. The laminated film according to claim 1, wherein, The haze of the laminated film is above 5% and below 35%.
6. The laminated film according to claim 1, wherein, The resin layer contains microparticles.
7. The laminated film according to claim 6, wherein, The average particle size is greater than 1 μm and less than 16 μm.
8. The laminated film according to claim 6, wherein, The difference between the refractive index of the matrix resin contained in the resin layer and the refractive index of the microparticles is greater than 0.00 and less than 0.
10.
9. The laminated film according to claim 1, wherein, The resin layer contains nanoparticles with an average particle size of less than 200 nm.
10. The laminated film according to claim 1, wherein, The substrate layer is a polyester film.
11. The laminated film according to claim 1, wherein, The laminated film is a writing feel enhancement film for touch panels.
12. A laminated sheet comprising: a laminated film according to any one of claims 1 to 11; and a protective film disposed on at least one side of the laminated film.
13. A laminated sheet comprising: a laminated film according to any one of claims 1 to 11; and an adhesive layer disposed on at least one side of the laminated film.
14. An image display device comprising a laminated film according to any one of claims 1 to 11.
Citation Information
Patent Citations
Writing-touch enhancing film
JP2018097670A